Cenas de enunciação e ethos discursivo: análise do discurso de autoajuda para adolescentes - Furlan, Marília Molina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research aims to analyze the discourse of self-help for teenagers, through theoretical and methodological apparatus of Discourse Analysis of French Line, with emphasis on reflections developed by Maingueneau about the notion of discursive ethos. We selected and describe four representative works of this discourse. The interest in the concept of discursive ethos, defined by Maingueneau (2005) as the image of the subject that states projects from himself by his enunciation, is justified by the role that image, linked to social stereotypes, plays in the process of adhesion of public to discourse, this is, the ethos is directly linked to the effectiveness discourse. In addition, ethos participates of the constitution of scenography of discourse, scene that discourse presupposes to be stated and that it validates by his own utterance. Considering aspects of linguistic materiality of the works of the corpus, the analysis reveals the heterogeneity both of ethe of self-help discourse for teenagers as the scenography articulated these ethe. The analysis also indicates that in the four surveyed works there are different ethe and scenography than those relating to self-help discourse for adults. Thus, in three of the analyzed works, we observe the attenuation of typical authoritative tone of this self-help discourse for adults. On the other hand, one of the works of the corpus, American work translated in Brazil, is closer to self-help discourse for adults, because it has the same authoritative tone that characterizes this type of self-help discourse

Esta pesquisa tem como objetivo analisar o discurso de autoajuda para adolescentes, por meio do aparato teórico-metodológico da Análise do Discurso de linha francesa, com ênfase nas reflexões que Maingueneau desenvolve sobre a noção de ethos discursivo. Para tanto, selecionamos e descrevemos quatro obras representativas desse discurso. O interesse pela noção de ethos discursivo, definido por Maingueneau (2005) como a imagem que o sujeito enunciador projeta de si pela sua enunciação, justifica-se pelo papel que essa imagem, ligada a estereótipos sociais, desempenha no processo de adesão do público ao discurso, ou seja, o ethos está diretamente ligado à eficácia discursiva. Além disso, o ethos participa da constituição da cenografia do discurso, cena que o discurso pressupõe para ser enunciado e que ele valida por sua própria enunciação. Considerando-se aspectos da materialidade linguística das obras do córpus, a análise revela a heterogeneidade tanto dos ethé do discurso de autoajuda para adolescentes quanto das cenografias articuladas a esses ethé. A análise também indica que se trata de ethé e de cenografias diferentes das relativas ao discurso de autoajuda para adultos. Assim, em três das obras analisadas, nota-se a atenuação do tom autoritário típico desse discurso, quando ele se dirige a adultos. Por outro lado, uma das obras do córpus, obra americana traduzida no Brasil, está mais próxima ao discurso de autoajuda para adultos, pois apresenta o mesmo tom impositivo que caracteriza essa vertente de discurso de autoajuda
Keywords: Linguística; Análise do discurso; Autoajuda; Autopercepção; Literatura para jovens; Discourse analysis